Toxic effects of methanolic and dichloromethane extracts of flowers and peduncles of stryphnodendron adstringens (leguminosae: Mimosoideae) on apis mellifera and scaptotrigona postica workers - de Souza, Tiago Favaro; Cintra, Priscila; Malaspina, Osmar; Bueno, Odair Correa; Fernandes, João B.; da Silva Almeida, Sheila Susan M. (Taylor & Francis, 2006)
Laboratory bioassays were conducted to evaluate toxicity of methanolic and dichloromethane extracts obtained from Stryphnodendron adstringens to Apis mellifera and Scaptotrigona postica workers. The extracts were incorporated into the diet of the bees for evaluation of mortality rates. The ingestion bioassays were made with three concentrations (0.002mg/g, 0.005mg/g and 0.01mg/g) for each bee species. The workers were kept in cages, with twenty workers per cage for each concentration tested. All bioassays had sixty workers in three cages that where maintained in a biological oxygen demand incubator with controlled temperature and humidity. The data obtained in the toxicity bioassays were analyzed statistically by Log Rank test and all methanolic and dichloromethane extracts showed significant (P<0.0001) toxic effects in all tested concentrations. © 2006 International Bee Research Association.
Keywords: Barbatimão; Botanical extracts; Honey bees; Toxicology